Design and development of POCN-pincer palladium catalysts for C-H bond arylation of azoles with aryl iodides - Khake, Shrikant M.; Soni, Vineeta; Gonnade, Rajesh G.; Punji, Benudhar (Dalton Transactions, 2014)
{Well-defined and efficient POCN-ligated palladium complexes have been developed for the direct C H bond arylation of azoles with aryl iodides. The phosphinite-amine pincer ligands 1-(R2PO)-C6H4-3-((CH2NPr2)-Pr-i) 1R2POCNIPr2-H; R = `Pr (1a)